Characteristics and risk factors for infection and mortality caused by Klebsiella pneumoniae in patients with acute pancreatitis - Jing Chen; Qian Xiang; Jia-yu Wu; Xiao-Jia Zheng; Xiao-yan Jiang (Frontiers in Public Health)
BackgroundThe purpose of this study is to investigate the risk factors for carbapenem-resistant Klebsiella pneumoniae (CRKP) infection and death of K. pneumoniae infections in acute pancreatitis (AP) patients.MethodsThis was a retrospective analysis of AP patients with K. pneumoniae infection between January 2019 and April 2024. Logistic regression model was used to determine the risk factors for acquisition of CRKP. Cox proportional hazards regression model was used to identify risk factors for mortality of K. pneumoniae infection.ResultsA total of 113 AP patients experienced K. pneumoniae infections, including 66 with CRKP infection and 47 with CSKP infection. The mortality rate of these patients was 36.3%, with a significantly higher mortality rate in the CRKP group than in the CSKP group (P < 0.001). Only mechanical ventilation (OR = 2.301; 95% CI 1.02-5.20; P = 0.045) was the independent risk factor for CRKP infection in patients with AP. Surgery (HR 0.38; 95% CI 0.20–0.75; P = 0.005) and mechanical ventilation (HR 2.93; 95% CI 1.10–7.82; P = 0.032) were the independent risk factors associated with mortality of K. pneumoniae infection in patients with AP.ConclusionKlebsiella pneumoniae infection has become a threat to patients with AP. Therefore, implementing preventive and control measures based on risk factors is crucial for the prognosis.